Contributions of alanine and serine to sulfuric acid-based homogeneous nucleation. (1st February 2021) - Cao, Hui; Liu, Yi-Rong; Huang, Teng; Jiang, Shuai; Wang, Zi-Hang; Liu, Ying; Feng, Ya-Juan; Huang, Wei
Abstract: New particle formation (NPF) is the main source of atmospheric aerosols, and amino acids have been detected as the important components of atmospheric particulate matter. However, the role played by amino acids with different functional groups in the initial events of nucleation remains unclear. In this study, the interactions of alanine (Ala) and serine (Ser), which differ structurally by one hydroxyl group, with sulfuric acid were studied at the M06-2X/6-311 + G (d, p) theory level. Structural and thermochemical analysis results show that in small clusters, the introduction of the Ser's hydroxyl groups leads to the synergistic effect, which promotes proton transfer and improves the stability of the clusters. With the increase of cluster's size, the synergistic effect gradually reduces, the introduction of hydroxyl groups hinders the formation of hydrogen bonds between amino and carboxyl groups of Ser molecules with sulfuric acid molecules, resulting in the steric effect, reducing the stability of the clusters. Atmospheric relevance analysis results show that the formation rates of the clusters are positively correlated with the concentrations of sulfuric acid and amino acid, but negatively correlated with temperature. The temperature dependence of (SA)m (Ser)m is lower than that of (SA)n (Ala)n (n, m = 1–2, n = m), indicating for small clusters, the synergistic effect improves the stability of the clusters and plays an important role in the formation rates. The formation rates of (SA)m (Ser)m are slightly lower than that of (SA)n (Ala)n (n, m = 3–4), indicating for large clusters, the steric effect reduces the stability of the clusters and the concentrations of amino acid and sulfuric acid, temperature have greater influence on the formation rates. Highlights: Synergistic effect enhances pre-nucleation clusters formation. Steric effect suppresses pre-nucleation clusters formation. Formation rates are positively correlated with the monomers' concentration. Formation rates are negatively correlated with temperature.